The mediating effect of exhaustion in the relationship between effort‐reward imbalance and turnover intentions: A 4‐year longitudinal study from Sweden - Leineweber, Constanze (J Occup Health, 2021)
OBJECTIVES: Earlier studies suggest that imbalance between effort and reward at work associates with exhaustion. Others have found that exhaustion increases turnover intentions; an important precursor of actual turnover that also associates with counterproductive work behaviors. Few, however, have studied the associations between effort‐reward imbalance (ERI) and employees’ intentions to leave their current employment, and whether exhaustion is underpinning that relationship. Here, we investigate the mediating role of exhaustion in the effort‐reward imbalance – turnover intentions relationship. METHODS: Data from three waves covering a time span of four years from the Swedish Longitudinal Occupational Survey of Health (SLOSH) were analysed using structural equation modeling. Cross‐lagged mediation analyses were conducted to estimate if associations from ERI to subsequent turnover intentions were mediated by exhaustion. Other causal directions (direct and reversed direct effects, reversed mediation) were also examined. RESULTS: A direct path from ERI T1 to turnover intentions T2 was found, but not from ERI T2 to turnover intentions T3. Additionally, results showed that ERI at time points T1/T2 associated significantly with exhaustion two years later (T2/T3). Also, exhaustion at T1 showed a small but statistically significant direct association with turnover intentions at T2 (no association was found between exhaustion T2 and turnover intentions T3). A small, but statistically significant indirect effect from ERI to turnover intentions was found (estimate 0.005; 95% CI 0.002‐0.010). CONCLUSIONS: Providing a good balance between effort and reward for workers is essential to protect employee health and help retain employees in the organization.